FRACTAL APPLICATIONS IN POPULATION GROWTH PROBLEMS USING TURBO - Mulyadi Mulyadi; Drs. Sunarto Usna, MMSI (Jurnal Sistem Informasi, 2001)
The author discusses the problem of the use of fractals in the problem of populationgrowth by drawing in a graphic display by using a mathematical formula that is theformula bifurcation Robert May.